Applications for Advancing Animal Ecology - Morrison, Michael L. (Book collections on Project MUSE., 2021)
"The authors consider individual organisms before considering habitats; they demonstrate how to apply such an approach to animal ecology in the field. The book is meant for wildlife professionals who are interested in exploring what kinds of insights this alternative approach can yield"--